Report on PRIMAX’s financial performance / Muhd Shafiq Ismail - Ismail, Muhd Shafiq (Faculty of Business and Management, 2019)
This study summarizes the PRIMAX’s Group and the Company background, and it carries some issues related to its financial performance such as PRIMAX carries some several financial risks after this company planned to perform its own financial statement. Furthermore, PRIMAX carries out research methodology by using financial analysis tools on the company’s balance sheet and income statement. The analysis tools that PRIMAX implement was year to year, index number trend and financial ratio. With these financial analysis tools, it would help us to compare what are the similarities and differences between Group and the Company based on their balance sheet and income statement, and highlighted their own strength and weakness based on their financial ratio. When both Group and the Company identified their own weakness based on its balance sheet and income statement, we should recommend Group and the Company about solution to avoid their weakness. This would help them to solve their financial problem and can perform their financial performance very well in the future. This provides conclusion and recommendation as the end of this chapter after discusses Group and the Company’s financial performance using analysis tools based on their result they implement.